The association between diets and periodontitis: a bidirectional two-sample Mendelian randomization study - Yang, Xiaoyu; Wang, Jingchan; Hong, Houlin; Feng, Xing; Zhang, Xiumei; Song, Jinlin (Frontiers in Genetics, 2024)
Background: Periodontitis, a complex inflammatory condition, has been associated with dietary habits and antioxidants. While the association between certain dietary patterns and periodontitis has been documented, the bidirectional relationship remains unclear. This study utilizes Mendelian randomization (MR) analysis to investigate the bidirectional associations between dietary factors comprising dietary antioxidants, and periodontitis.Methods: Employing a two-sample MR approach, this study analyzed genome-wide association study (GWAS) data on diets and periodontitis from large databases and published literature.Instrumental variables (IVs) were selected and filtered based on genetic variants associated with dietary factors and periodontitis, respectively. Various MR methods, including Inverse Variance Weighted, MR-Egger, Weighted Median, Weighted Mode, and Simple Mode were applied to assess the bidirectional associations. Sensitivity analyses were conducted to validate the robustness of the findings.Results: Our analysis revealed significant associations between certain dietary factors and the risk of periodontitis. Specifically, higher intake of filtered coffee, low-calorie drinks, and other cereals, as well as increased metabolic circulating levels of gamma-tocopherol, were associated with an elevated risk of periodontitis. Conversely, consumption of cheese, white rice, chocolate bars, unsalted peanuts, and higher absolute circulating levels of vitamin C were linked to a reduced risk. Additionally, the study suggests that periodontitis may influence dietary habits, indicating a bidirectional relationship.This study provides additional evidence of a bidirectional association between dietary factors and periodontitis. It highlights the importance of dietary interventions in the prevention and management of periodontitis. The findings underscore the need for incorporating dietary counseling into periodontal disease management protocols and suggest the potential of personalized dietary strategies for periodontitis patients. Further research is warranted to explore the mechanisms underlying these associations and to confirm these findings in diverse populations.